Jogos Digitais - Teoria e Conceitos para uma Mídia Indisciplinada - Branco, Marsal Avila Alves (Universidade do Vale do Rio dos Sinos, 2011)
Proposes a theory of digital games. To do so, presents an analysis framework that divides games into three instances - production, interpretation and discourse - and the three dimensions - logical, aesthetic and technological. Instances allow us to think the games as communication products and therefore affected by social, political, economic, aesthetic and technological aspects, serving as the entry point of the facts of the world 'outside' into production, speech and play games. The dimensions concern on the diferent manners how this production, speech and enjoyment happen and relate to specific internal language of games. For these are proposed the concepts of Ludema / system rules, vividness / interactive, discursive structures and discursive manifestations. The two level structure (instances and dimensions) allows you to tackle the phenomenon of media either from its internal affectations - logic, aesthetics and technology tensing up and modifying - as well as a more general level by showing how each dimension is also a response to external forces departing from a socio-cultural context. The construction of this conceptual framework allows the design of a digital game theory, shows its fundamental concepts, their modes of internal relations, its connections with the outside world and modes of operation.
Keywords: System of rules; Theory of games; Games; Sistema de regras; Ludemas; Teoria de jogos; Metodologia de jogos; Game studies; Jogos digitais; ACCNPQ::Ciências Sociais Aplicadas::Comunicação